CITY BRANDING BERBASIS LOCAL WISDOM DALAM KAMPANYE “BETTER BANYUMAS” - Ascharisa Mettasatya Afrilia (Universitas Lambung Mangkurat, 2018)
Branding strategies in the context of marketing are important. Not only to label a product to be more valuable, a branding strategy is also important to position the product in the scope of the market itself. Increasingly, branding strategies also began to be applied to many lines. The existence of a place is also considered important to adopt a branding strategy to define itself in regional character. This definition is known as the city branding.. Banyumas, as one of the cities in the Central Java region, realizes the importance of city branding to instill a philosophy of local wisdom with the campaign that is promoted